2022
DOI: 10.1016/j.chb.2021.107035
|View full text |Cite
|
Sign up to set email alerts
|

Cybervictimization and well-being among adolescents during the COVID-19 pandemic: The mediating roles of emotional self-efficacy and emotion regulation

Abstract: Cybervictimization has been linked to adverse psychological consequences but little is known about the mechanisms linking cybervictimization to lower well-being. We conducted two studies to examine emotional self-efficacy and distinct emotion regulation strategies as potential mediators in the relationship between cybervictimization and lower well-being among German adolescents during the school closures due to the COVID-19 pandemic in early 2020. In Study 1, 107 adolescents ( M age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 73 publications
3
28
0
Order By: Relevance
“…Therefore, we cannot generalize our results to the entire Portuguese population, since a sampling bias might have occurred. Notwithstanding, our data is in line with other studies, as mentioned, that found similar mediation effects for emotional regulation strategies in completely diverse samples [21,22,59,60]. Finally, another limitation of our study was the lack of a priori sample size power analysis.…”
Section: Limitations and Strengthssupporting
confidence: 87%
“…Therefore, we cannot generalize our results to the entire Portuguese population, since a sampling bias might have occurred. Notwithstanding, our data is in line with other studies, as mentioned, that found similar mediation effects for emotional regulation strategies in completely diverse samples [21,22,59,60]. Finally, another limitation of our study was the lack of a priori sample size power analysis.…”
Section: Limitations and Strengthssupporting
confidence: 87%
“…Such distribution that more younger and urban responders are common in network survey in other published studies ( 47 , 48 ). In addition, the moderating analysis apply a bootstrapping method with 5,000 samples that is statistically robust against of non-normally or fairly distributed data ( 49 , 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…The lower the level of parental attachment, the higher the loneliness and the more cyberbullying behaviors. In particular, during the COVID-19 pandemic, emotional self-efficacy and emotion regulation mediate the relation between cyber victimization and well-being among youths (Schunk et al, 2021 ). This study suggests that we should prioritize reducing individual loneliness when preventing and providing intervention for cyberbullying.…”
Section: Discussionmentioning
confidence: 99%